2011
DOI: 10.4161/auto.7.11.16642
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus nsp6 proteins generate autophagosomes from the endoplasmic reticulum via an omegasome intermediate

Abstract: Autophagy is a cellular response to starvation which generates autophagosomes to carry cellular organelles and long-lived proteins to lysosomes for degradation. Degradation through autophagy can provide an innate defence against virus infection, or conversely autophagosomes can promote infection by facilitating assembly of replicase proteins. We demonstrate that the avian coronavirus, Infectious Bronchitis Virus (IBV) activates autophagy. A screen of individual IBV non-structural proteins (nsps) showed that au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
292
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(309 citation statements)
references
References 44 publications
13
292
0
4
Order By: Relevance
“…However, autophagosome-like vesicles were rarely observed in the mock-infected cells (Figure 1A). It is well known that coronavirus infection can induce a large number of double-membrane vesicles (DMVs), and the functional link between autophagic DMVs and coronavirus-induced replication-associated DMVs remains controversial [22,23,24]. In this study, these two different DMVs might co-exist in PEDV-infected cells [25].…”
Section: Resultsmentioning
confidence: 96%
“…However, autophagosome-like vesicles were rarely observed in the mock-infected cells (Figure 1A). It is well known that coronavirus infection can induce a large number of double-membrane vesicles (DMVs), and the functional link between autophagic DMVs and coronavirus-induced replication-associated DMVs remains controversial [22,23,24]. In this study, these two different DMVs might co-exist in PEDV-infected cells [25].…”
Section: Resultsmentioning
confidence: 96%
“…Live imaging experiments suggested that at least some autophagosomes are formed within omegasomes. Subsequent work suggested that several pathogens known to induce autophagy also induce omegasomes, whereas depletion of WIPI2 (a mammalian equivalent of Atg18) increases omegasome numbers [40,43,44]. Finally, DFCP1 and WIPI2 co-localize on omegasomes and neither becomes part of mature autophagosomes [40].…”
Section: Omegasomes Are Ptdins3p-enriched Autophagosome Platformsmentioning
confidence: 94%
“…Further to this, another recent study (Cottam et al, 2011) demonstrated that the nsp6 protein of various coronaviruses (including the SARS coronavirus), or the nsp5-7 protein of the arterivirus, porcine reproductive and respiratory syndrome virus (PPRSV), located to the ER where they recruited Vps34 and DFCP1, leading to omegasome formation. Our data complement this study and we propose therefore that the similarities between HCV and coronavirus or arterivirus membrane rearrangements may, at least in part, be explained by a common mechanism of biogenesis of these membrane structures.…”
Section: Discussionmentioning
confidence: 99%